Targeting Immunometabolism in Glioblastoma - Mohan, Aditya A.; Tomaszewski, William H.; Haskell-Mendoza, Aden P.; Hotchkiss, Kelly M.; Singh, Kirit; Reedy, Jessica L.; Fecci, Peter E.; Sampson, John H.; Khasraw, Mustafa (Frontiers in Oncology, 2021)
We have only recently begun to understand how cancer metabolism affects antitumor responses and immunotherapy outcomes. Certain immunometabolic targets have been actively pursued in other tumor types, however, glioblastoma research has been slow to exploit the therapeutic vulnerabilities of immunometabolism. In this review, we highlight the pathways that are most relevant to glioblastoma and focus on how these immunometabolic pathways influence tumor growth and immune suppression. We discuss hypoxia, glycolysis, tryptophan metabolism, arginine metabolism, 2-Hydroxyglutarate (2HG) metabolism, adenosine metabolism, and altered phospholipid metabolism, in order to provide an analysis and overview of the field of glioblastoma immunometabolism.